2001
DOI: 10.1002/1522-2594(200103)45:3<383::aid-mrm1050>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Changes in apparent diffusion coefficients of metabolites in rat brain after middle cerebral artery occlusion measured by proton magnetic resonance spectroscopy

Abstract: Diffusion‐weighted proton MR spectroscopy and imaging have been applied to a rat brain model of unilateral middle cerebral artery occlusion between 1 and 4 hr post occlusion. Similar apparent diffusion coefficients (ADC) of most metabolites were observed within each hemisphere. In the ischemic ipsilateral hemisphere, the ADCs were (0.083–0.116) · 10–3 mm2/sec for lactate (Lac), alanine (Ala), γ‐amino butyric acid (GABA), N‐acetyl aspartate (NAA), glutamine (Gln), glutamate (Glu), total creatine (tCr), choline‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 30 publications
7
50
3
Order By: Relevance
“…The lower temperature of 20°C used in this study would cause the ADC of the metabolites examined to be lower than they would be at physiological temperature of the human brain. Also, the ADC values of the metabolites in in vitro frog nerve could theoretically be less than in vivo prior to excision given the known reductions ($30%) in metabolite ADC after stroke in rodent models [9][10][11][12][13][14][15]. Furthermore, studies in rat trigeminal nerve have shown an $20% decrease in pseudo Trace/3 ADC of water post mortem [24], so a similar decrease might be expected for metabolites in excised nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower temperature of 20°C used in this study would cause the ADC of the metabolites examined to be lower than they would be at physiological temperature of the human brain. Also, the ADC values of the metabolites in in vitro frog nerve could theoretically be less than in vivo prior to excision given the known reductions ($30%) in metabolite ADC after stroke in rodent models [9][10][11][12][13][14][15]. Furthermore, studies in rat trigeminal nerve have shown an $20% decrease in pseudo Trace/3 ADC of water post mortem [24], so a similar decrease might be expected for metabolites in excised nerve.…”
Section: Discussionmentioning
confidence: 99%
“…DTI of tissue water includes contributions from exchanging intraand extracellular water, which makes compartment specific interpretation of diffusion characteristics rather complex. It has long been shown that reductions in water diffusion are a sensitive indicator of early cerebral ischemia [8], and despite the theory that this decrease is due to a water shift from extra-cellular to intra-cellular space, purely intracellular metabolites also show a reduction of diffusion by a similar magnitude without any compartmental shifts [9][10][11][12][13][14][15]. These metabolite diffusion studies are usually interested in either single direction diffusion or rotationally invariant mean diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the apparent diffusion coefficient (ADC) as measured by DW-NMR potentially depends on a wide variety of parameters that might be characteristic of different compartments, such as intracellular viscosity and tortuosity, restriction by or exchange through membranes, vesicle diffusions, or even cytoplasmic streaming. This expected sensitivity to cellular and subcellular properties has motivated various studies aimed at measuring metabolite ADC in the normal brain (2)(3)(4)(5)(6)(7)(8)(9)(10) or under perturbative conditions such as ischemia (11)(12)(13)(14)(15)(16), excitotoxic injury (13), tumor (16), or variation of the anesthesia level (17). However, although there is little doubt about the actual existence in the brain of compartments with different diffusion properties, they have not been clearly identified, and the extent to which DW spectroscopy effectively allows them to be probed in vivo remains to be explored experimentally.…”
mentioning
confidence: 99%
“…It has long been shown that reductions in water diffusion are the most sensitive indicator of early cerebral ischemia (6), and that despite the theory that this decrease is due to a water shift from extra-cellular to intra-cellular space, purely intra-cellular metabolites also show a reduction of diffusion by a similar magnitude without any compartmental shifts (4,(7)(8)(9)(10)(11)(12). Thus, diffusion-weighted spectroscopy can add insight into the biophysical properties of diffusion in tissue, but it remains to be tested whether or not diffusion of intra-cellular metabolites will provide evidence of neuronal/axonal abnormalities in the absence of changes in either water diffusion or other MR properties in a variety of neurologic disorders beyond ischemia.…”
mentioning
confidence: 99%